KETIDAKMAMPUAN TOKOH SELENA DALAM MEMPRESENTASIKAN KESEIMBANGAN ID DAN EGO PADA NOVEL SELENA: PERSEPEKTIF PSIKOANALISIS FREUD - Sanggam, Shella (Jurnal Pena Indonesia, 2024)
The aim of this study was to find out the language errors in the article entitled implementation of this research focuses on the character of Selena who struggles to balance her id, ego, and superego. The aim of this research is to examine the id, ego, and superego within the character of Selena. The research method used is descriptive qualitative with secondary data sources (the novel “Selena”). The results of this scientific paper show several pieces of evidence that the character of Selena experiences an inability to balance her id, ego, and superego. This research provides insight that all humans have their own id, ego, and superego, and not all humans can stabilize these three aspects. Keywords: id, ego, and superego